ESTIMATION OF INDICES OF QUALITY OF WORK OF HEAT PUMP WITH VORTEX TUBE - Sit M.L.; Ioisher A.M.; Sit B.M. (Problems of the Regional Energetics)
It is performed analisys of the use of efficiency of the use of vortex tube in heat pump with carbon dioxide as the refrigerant. Heat pump is desinated for parallel production of of heat on one temperature level and cold on two temperature levels. Scheme is compared with heat pump in which ejectors are used. It is demonstrated on the exemple that scheme with the vortex tube has COP increased comparitive with those with ejectors.